Role of Silver Stream in Healing Diabetic Ulcers - Ashwani Kumar; Satinderjit Singh Bajaj; Jagminder Kaur Bajaj (New Advances in Medicine and Medical Science Vol. 4, 2023)
This chapter aims to compare effectiveness of dressing with silver stream solution versus povidone iodine in healing of diabetic ulcers. Diabetic ulcers affect morbidity, mortality & quality of life (QOL) of diabetic patients. Contamination of ulcers with pathogenic organisms disturbs healing process . Thus wound debridement and dressing using antiseptics, constitutes an important aspect of treatment. Povidone iodine is a widely used antiseptic for wound dressings. Silver stream, solution containing ‘silver ions, menthol, glycerol & surfactant’ has shown promising results in chronic DFU. In this study, 100 patients with diabetic ulcers were randomly divided into 2 groups of 50 each. Group A received, ulcer dressing with silver stream solution & group B with povidone iodine, every 48 hours. Effect of drugs on ulcer size & healing was evaluated at 2 weeks intervals for 8 weeks or till ulcer healed . Patients of Group A & B were comparable in terms of their age , sex distribution, duration of diabetes and pretreatment mean ulcer sizes. Maximum patients were in age group of 51-60 years. About 3/4th of patients had spontaneous onset of ulcer in both the groups. A progressive significant reduction in mean ulcer size occured in both the groups but % age reduction was much more in group A (89.51%) than in group B (33%) at 8 weeks (P<0.05). There was significant difference in healing rates in group A & B. All patients in group A responded to silver stream treatment, though response was partial in 10%. Patients having poor glycemic control. In contrast, in povidone iodine group, 12% did not responded, 42% had partial response & only 46% showed complete response. Response rate with silver stream is significantly higher than povidone iodine. Silver stream dressing causes significantly more reduction in mean ulcer size at end of 8 weeks treatment than povidone iodine.